2020
DOI: 10.1002/eji.201948393
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor receptor family costimulation increases regulatory T‐cell activation and function via NF‐κB

Abstract: Several drugs targeting members of the TNF superfamily or TNF receptor superfamily (TNFRSF) are widely used in medicine or are currently being tested in therapeutic trials. However, their mechanism of action remains poorly understood. Here, we explored the effects of TNFRSF co-stimulation on murine Foxp3 + regulatory T cell (Treg) biology, as they are pivotal modulators of immune responses. We show that engagement of TNFR2, 4-1BB, GITR, and DR3, but not OX40, increases Treg proliferation and survival. Triggeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 57 publications
3
57
0
Order By: Relevance
“…Nevertheless, both receptors (predominantly TNFR2) can activate the NF-κB signaling pathway via the involvement of TNF receptor-associated factors (TRAFs) [61]. It has been demonstrated that TNFR family co-stimulation increases regulatory T cell activation and function via NF-κB [62]. Moreover, it was shown that the NF-κB RelA subunit (p65) transcription factor is critical for T reg activation and stability [63].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, both receptors (predominantly TNFR2) can activate the NF-κB signaling pathway via the involvement of TNF receptor-associated factors (TRAFs) [61]. It has been demonstrated that TNFR family co-stimulation increases regulatory T cell activation and function via NF-κB [62]. Moreover, it was shown that the NF-κB RelA subunit (p65) transcription factor is critical for T reg activation and stability [63].…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that one of the most important regulators of T regs activity is TNFR2 which is directly related to their activation and immunosuppressive function. 82,[87][88][89] Interestingly, we found that both the percentage and expression level of TNFR2 was signi cantly higher on Foxp3 + CD4 + iT regs after co-culture with FL-MSCs than with BM-MSCs ( Figure 5). The same results were observed for CD25, GITR and ICOS markers demonstrating a higher global activation of iT regs derived from FL-MSCs than BM-MSCs (Figure5).…”
Section: Fl-mscs Induced It Regs Display a More Active Phenotype Thanmentioning
confidence: 87%
“…We also checked the expression of TNFR2, one of the most important regulators of T regs activity, that has been shown by us and others to be directly related to their activation and immunosuppressive function 81,86,87 . We found that the percentage and expression level of TNFR2 was signi cantly higher on CD4 + Foxp3 + iT regs induced by FL-MSCs than with BM-MSCs, re ecting a global activation of the T reg induced population.…”
Section: Discussionmentioning
confidence: 99%